Survival of newborn mice testes during allotransplantation under kidney capsule or into testis of adult animals - Пахомов, O. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
In this study, we carried out a comparative analysis of the graft survival and the development of the testes of newborn animals in immune privileged organs, such as the testes of adult animals, versus their survival in non-immune privileged organs, such as the kidney capsule. The grafts under kidney capsule did not develop. They were acutely rejected for 2 weeks after transplantation. The testis of the newborn mice developed only under the intratesticular transplantation. Fifteen days after the transplantation, the primary spermatocytes formed in the seminiferous tubules of grafts which had been transplanted into the testes. Subsequently, the growth of immunological rejection led to slow destruction of seminiferous tubules. According to the manner of the reactions, it was a chronic rejection, which was evidenced by the presence of donor cells after 60 days under the transplantation and the absence of foci of the lymphocytic infiltration. The cellular mechanism of the acute rejection was not fulfilled completely after the intratesticular transplantation. It was demonstrated that the testes of adult individuals could be used as a site for transplantation, which can prolong donor grafts survival. Moreover, the testes of newborn individuals can be used as potential objects of intratesticular transplantation.